Mitologizacja pamięci. Wokół sporu o ocenę polskiego i litewskiego ruchu oporu - Jundo-Kaliszewska, Barbara (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
Regarding the dispute about the evaluation of the Polish and Lithuanian resistance. The article presents a number of introductory insights into the subject of forming mutually negative portrayals of the two nations in the period of II World War. Having considered threats resulting from unresolved international conflicts, I point out the reasons for the Polish-Lithuanian exemplified by mutual relations of representatives of the resistance movement of both nations, who were involved in resistance activities during World War II on the territory of the contemporary Vilnius region. At the same time I attempt to specify and systematize the facts from the history of Lithuanian armed formations operating in Lithuania during the period of interest. Particular emphasis is placed on the role of Lithuanian partisans in collective memory of the both Lithuanians and the local Polish minority. I treat this text as a contribution and an encouragement to discuss and intensify research in this area. Issues raised here that would seem long gone, still play a huge role in the politics of Poland and Lithuania and have an impact on the future of our region, especially in the context of international security.